Management of Acute Pancreatitis in Critical Care Unit - Güniz Meyancı Köksal (Türk Yoğun Bakim Derneği Dergisi, 2010)
Pancreatitis is characterized by an inflammation occuring due to digestion of pancreatic self tissues and other organs after activation of digestive enzymes which are stable under normal conditions . For all the pancreatitis cases, the mortality rate is <%15. In the acute pancreatitis cases, the monitorization of the inspiration system, cardiovascular system and the metabolic status are needed. There is no primary therapy for the pancreatitis. All the therapy protocols are support therapy. The basic support therapy methods are: Liquid replacement, respiration support, pain management, pancreas secretion inhibition, metabolic support, intra-abdominal monitoring and decompression, nutrition, antibiotherapy, immunomodulation, coagulation mechanism monitoring. In the acute pancreatitis, the causes of early deaths are pancreatic shock and acute pulmonary thrombohemorrhage, within the first 7 days the causes of the 75% deaths are pulmonary shock and congestion and after 7 days the causes of the 77% are pancreas abscess, MOF (multiple organ failure), purulent peritonitis and erosive hemorrhage. (Journal of the Turkish Society of Intensive Care 2010; 8: 85-9)